Has trade openness reduced pollution in China? - Sandra Poncet; Laura Hering; José De Sousa (Fondation pour les études et recherches sur le développement international (FERDI), 2015)
We use recent detailed Chinese data on trade and pollution emissions to assess the environmental consequences of China's integration into the world economy. We rely on a panel dataset covering 235 Chinese cities over the 2003-2012 period to see whether the environmental repercussions from trade openness depend on whether the latter concerns processing or ordinary activities. In line with our theoretical predictions, we find a negative and signicant effect of trade on emissions that is larger for processing trade and activities undertaken by foreign firms: the environmental gains from either ordinary trade activities or domestic firms are much lower, even though these today represent the main drivers of China's export and import growth. This result suggests some caution regarding pollution prospects in the context of the declining role of processing trade.
Keywords: F10; F14; O14; 330